أثر الدرس اللغوي عند ابن عرفة الورغمي رحمه الله في تفسيره - فاطمة زهرة سناينة (University of eloued جامعة الوادي, 2025)
"هذه الدراسة موسومة: "" أثر الدرس اللغوي عند الإمام ابن عرفة الوَرْغَميّ -رحمه الله- في تفسيره "". وقد درات حيثياتها حول علاقة العمل التفسيري باللغة عند أحد أعلام المغرب العربي؛ وهو الإمام ابن عرفة الوَرْغَميُّ الذي عرف بتمكنه في اللغة وعلوم الدين، وصغتها كالآتي: كيف عني الإمام ابن عرفة في تفسير القرآن الكريم باللغة وأثرها في الكشف عن معانيه وبيان بلاغته؟ وما هي أبرز هذه المباحث اللغوية التي برزت في تفسيره؟ وقد جاءت خطة البحث مكونة من مقدمة وفصلين وخاتمة؛ الفصل الأول: "" ابن عرفة ومنهجه في التفسير"". والفصل الثاني: "" توظيف الإمام ابن عرفة للمباحث اللغوية في تفسيره"" ومن أهم النتائج المتوصل إليها: أن تفسير الإمام ابن عرفة قد زخر بمختلف فروع علوم اللغة دلالة ونحو وصرفا وبلاغة وأساليب .... فكان يوظفها بحرص في فهم المعنى والوقوف عند أصوبه مقصدا. This study is entitled The Effect of the Linguistic. Lesson on the Interpretation of Quran by Imam IBN ARAFA AL-OUARAGHMI; May God have mercy on him ' It's details are about the relationship between interpreting work and language according to Imam IBN ARAFA Al-Ouaraghmi who was well-known for his mastery of language and religious science. It's structure was as follows; how did Imam IBN ARAFA focus on language in interpreting Quran to show its meaning and clarify it's eloquence ? What are most prominent linguistic topics provided in his interpretation ? The research outline is composed of an introduction; two chapters; and a conclusion. The first chapter is entitled IBN ARAFA His Approach to Interpretation and the second one is IBN Arafa's use of Linguistic topics appeared in his Interpretation . One of the major results reached is that Imam IBN Arafa's Interpretation was rich of various linguistic streams and branches including grammar; semantics ; morphology; éloquence ; and styles... He used them carefully in understanding the meaning and determining the rightest one.
Keywords: التفسير; ابن عرفة؛ الورغمي; الدرس؛ اللغوي; the Interpretation; Imam IBN ARAFA; AL-OUARAGHM; Lesson